STRATEGI PENGEMBANGAN USAHA SONGKOK RECCA DI KECAMATAN AWANGPONE KABUPATEN BONE - Kardianto, Kardianto; Muhammadiah, Muhammadiah; Mone, Ansyari (Universitas Muhammadiyah Makassar, 2022)
This research aims to determine the business development strategy of songkok recca. This subject uses descriptive qualitative research type. Data collection used are observation, interview and documentation. This research showed the result that songkok recca business development strategy in Awangpone subdistrict and department of cooperative and UMKM Bone regency still not maximal in development of songkok recca business. There are 3 strategic aspect: 1) cost leadership ( can be seen in terms of service, fleet sales and advertising), 2) differentiation strategy product ( to win the competition by making unique product, physical quality and cultural value), and 3) focus strategy (which the focus on the buyer group and the product line segment, or the geographic market (special market of songkok recca product sales).